Triggering sustainability communication in a B2B context: combining action research and sensemaking - Apostol Oana; Mäkelä Marileena; Heikkilä Katariina; Höyssä Maria; Kalliomäki Helka; Jokinen Leena; Saarni Jouni (Emerald, 2022)
Purpose The paper explores processes associated with the adoption of corporate sustainability communication in a B2B context. It employs a combined action research and sensemaking approach to document moments that precede the initiation of external sustainability communication.
Design/methodology/approach The paper is the outcome of an action research project, where we examine the case of one industrial company that was silent on its multiple sustainability-related practices, but recently decided to become more transparent to the outside world. A processual approach to sensemaking is adopted to show how organisational and non-organisational members actively participated in meaning co-construction.
Findings Corporate silence can be disrupted by triggering events that cause moments of sudden realisation for organisational members, eventually leading to the initiation of sensemaking processes inside the organisation. Once this occurs, the possibility of externally communicating sustainability appears a feasible and strategic approach to pursue. We document how different actors are involved in meaning co-construction and how the entire process of sensemaking unfolds.
Practical implications A sensemaking approach sheds light on the complexity of sustainability communication, where multiple actors are involved. This is a useful approach to consider in order to couple sustainability with other organisational practices. Moreover, sensemaking opens a window of opportunity for various societal actors' interventions to shape the role and content of sustainability communication.
Originality/value The paper offers an original, theoretically informed methodological contribution to the literature on sustainability communication by coupling a sensemaking approach with action research. The approach is employed to examine the role of internal organisational actors in sustainability reporting processes, an area that has received scant attention.